Pembuatan Website Berbasis Elementor Di SD Kanisius Keprabon 01 Surakarta - Purbasari, Dita Anggi; Nugraha, Dava Gilang (Politeknik Indonusa Surakarta, 2022)
The purpose of this research is to design a school website for SD Kanisius Keprabon 01 Surakarta which will be operated to promote its school. The reason why the writer decides to design a website is since the implementation of school zoning system, the number of students of SD Kanisius Keprabon 01 Surakarta decreases year by year. The solution to overcome this problem is to design a school website in order to reach a wider range. Website is an effective way to do a promotion because a website provides various information that can be searched for by users and it also provides an online students’ registration which can be done anywhere. This website is designed by using Elementor. According to Imas Indra (2021) Elemnetor is page builder which is specifically used to design a website based on WordPress. The writer uses Elementor because it provides various elements which will be useful to be used by user to operate this website.